Re-thinking gender : feminist representation of gender paradoxes in selected novels by Emecheta and Adichie - Masha, Lethabo (My University, 2024)
This study is a qualitative enquiry on the paradoxes brought about by the hegemonic concept of gender, which are fundamentally based on the differences of biological sex. Gender ideology proves to be problematic in the ways in which it facilitates inequality in African societies. The problem identified and addressed by this study is that dominant gender ideals are to a large extent, imposed and influenced by colonialism in many African countries. Furthermore, the way in which contemporary African cultural ideologies facilitate gender disparity demonstrates that they are diluted products of the interface of the native and coloniser. In line with these views, this research sought to reimagine gender ideologies through a thematic analysis of Emecheta’s Double Yoke (1983) and The Joys of Motherhood (1979), as well as Adichie’s Purple Hibiscus (2003) and Americanah (2013). These novels were purposively sampled due to their impactful contribution to African literature which advocates for gender equality in the continent and diaspora. Moreover, the novels explore different plights of black women throughout the pre-colonial, colonial as well as post-colonial era, from early advocacy against sexist labour restrictions to contemporary issues of imperial aesthetics. African centred perspectives of Womanism and Stiwanism were employed as theoretical lens to analyse the literature discussed as well as the chosen literary texts. The analysis and review of the selected literature demonstrates that since the incursion of colonialism, African men and women were juxtaposed against white/European men and women and in that way, the former were re-constructed through a modification driven by Western ideologies. In addition, the study examined how African and Western cultures as well as religions perceive gender with regard to chastity, marriage and parenthood. The analysis of Double Yoke revealed that black women in post-colonial Nigeria, are confronted with the burden of establishing identities within a society that is filled with contradicting traditional and modern ideologies. Matladi (2022) explains that even with constitutions based on human rights, many post-independence African states embody patriarchy in various ways. The Joys of Motherhood on the other hand, exposed how colonialism tempered with African practices of marriage (monogamy and polygyny), son preference as well as the othering of women in their role as mothers. Purple Hibiscus mainly exposes the toxicity of a patriarch who forces his subjects into submission through physical and psychological abuse. Lastly, Adichie uses Americanah to portray the struggles of black women in the diaspora whereby their existence as black and female continues to be used as a discriminatory tool even in the 21st century. Moreover, in the African context, traditional ideologies of approved femininity perpetually bolster the marginalisation of females in the private and public spaces. The current study is distinguished by its adoption of African centred theoretical perspectives to analyse the selected literature, particularly in its deviation from the redundant critiques of universalising gender and validity of feminist and womanist theories in the African context. The current research undertaking recommends that studies on African societies must be actively committed to the liberatory practice of decolonising sex and gender ideologies in their attempt to debunk the myth of African societies and cultures as naturally and inherently patriarchal. Furthermore, indigenous African cultures should cease to be cited as justifications for gender bias but instead, should be seen as having an ability to evolve. And lastly, while black people in Africa and diaspora may share some commonalities, their experiences should be accurately analysed by considering their differences.
Thesis (Ph.D. (English Studies)) -- University of Limpopo, 2024
Keywords: Femininities; Gender construction; Gender Ideology; Gender inequality; Masculinities; Sex; Ferminism; Paradoxes; Equality; Paradox in literature